HUBUNGAN PRAKTIK SUPPLY CHAIN MANAGEMENT (SCM) DAN KNOWLEDGE MANAGEMENT (KM) TERHADAP KINERJA ORGANISASI (Studi Literatur) - Erni Alfisah; Aida Vitria; Siti Mardah; Basuki Basuki (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
This research is a literature study that aims to examine the relationship of supply chain management practices to organizational performance and investigate the impact of process knowledge management as a mediator in determining this relationship. The seven dimensions of supply chain management practices were used to investigate the effects of the two different dimensions on organizational performance whereas the three dimensions of process knowledge management were used as testers of mediating relationships. The results show that supply chain management practice of information sharing, quality information sharing and real practices related to the financial and non-financial performance of the organization. Three dimensions of the knowledge management process were found to mediate the relationship between information sharing, quality of information sharing and actual practices on non-financial performance of organizations. In addition, only one dimension of the knowledge management process, namely applied knowledge, mediates the relationship between subscription relationships, information sharing, information quality sharing and actual practice on organizational financial performance. Theoretical implications of this paper are factors that have a greater influence on organizational performance and practical implications allow practitioners to create practices whose effectiveness is studied to help improve organizational performance. Recommendations for future research including other measurement factors can be assessed using statistical tests.